ANALISIS PERAN DAN MANFAAT PABRIK RICE TO RICE (RTR) PROGRAM BULOG NTB TERHADAP KEBERLANJUTAN USAHATANI PADI DI KECAMATAN SIKUR - Herdiana, Herdiana; Andiana, Baiq Dewi Lita (AGRIBIOS, 2025)
This research aims to analyze the influence of the benefits and role of the BULOG NTB RTR program factory on the sustainability of farming. This research is quantitative research. This research uses primary data obtained through questionnaires, counseling and Forum Group Discussion (FGD). The population of this study were farmers in the 7 villages closest to the Rice to Rice (RTR) factory location. The sampling technique in this research uses purposive sampling. The sample obtained was 70 respondents. The data was processed using statistical software for social science (SPSS) version 25. The results of this study show that the influence of benefits, convenience and attitude has a positive and significant effect on interest in using the RTR factory, the influence of benefits and convenience variables has a positive and significant effect on attitudes, and The results of the path analysis test of the attitude variable can mediate the influence of benefits and convenience on farmers' interest in using the RTR factory as a place to sell produce with statistical analysis results (X1) of 0.115 which is positive and the level of significance in the t test is 0.000 < 0.05, ease (X2) of 0.368 which has a positive sign and a significance level of 0.000 <0.05, and the influence of interest (X3) of 0.412 which has a positive sign with a significance level of 0.000 <0.05. And based on the Sobel test, it is known that attitude mediates benefits on interest, with a calculated t value of 1.3052 > from the t table value of 1.2881 and attitude mediates convenience towards farmers' interest in using the RTR factory with a calculated t value of 1.4372 > from t table 1, 2610. There are 5 important factors that influence farmers in making the decision to sell their crops to the RTR factory, namely price, RTR factory policy that does not impose burdens on farmers, openness of factory access to farmers, sustainability, involvement of farmers in changing factory policies. The results of the outreach raised farmers' hopes for the future in the RTR factory where 57.14% of the socialization of the RTR Factory must be carried out by involving farmers, village collaboration with the RTR factory is open and sustainable and the results of the FGD showed 5 problems raised and solutions provided for the benefit of the RTR factory in Sikur district. The benefits of the BULOG NTB Rice to Rice (RTR) factory for farmers and the community. The results of questionnaires and the results of in-depth interviews with farmers and farmer groups show that the benefits of the BULOG NTB RTR factory have not yet been felt in real terms because the socialization of the factory program has not been evenly distributed.